University Museum: it’s relevance as an enhanced learning ecosystem for higher education / Wahiza Abdul Wahid … [et al.] - Abdul Wahid, Wahiza; Maliki, Muhammad Ammar; Manan, Juliana; Mat Isa, Mohd Jamil (Faculty of Art & Design, 2022)
The most interesting museum exhibitions are fun exhibitions, and when visitors start to feel that there are many things to explore and benefit from their tours. Like other countries, Malaysia has a wide variety of museums, one of which is the university museum that serves as a learning and research center. With the establishment of MyMuse (Museums and Galleries of Malaysian Public Universities), efforts are made to meet academic needs. However, the role of university museums and galleries in this contemporary era is constantly changing over time. The 21st-century university museums should now try to improve relations with the university and local communities and provide extraordinary exhibits and collections to be accepted internationally. The objectives of this study are to explicate to what extent the university museums and galleries are still relevant in benefiting the surrounding community and to identify the methods used in the process of skill development, learning experiences, and exploration of ideas at Malaysian university museums. A qualitative approach was employed through interviews involving 19 museum personnel from 13 university museums and galleries throughout Malaysia. From the study, it is observed that the university museums and galleries strive to achieve the objectives set by the management in ensuring that they remain relevant, playing their roles, providing students with information, and enabling them to conduct research. These institutions can now produce dynamic exhibitions although some may have barriers in terms of expertise and expenditure. Nonetheless, these museums are still trying to expand the methods of operation in more economical ways and benefit many.